Enhanced selective removal of phosphate in the presence of high-strength nitrate using straw-based anion imprinted biosorbent. Issue 3 (June 2022) - Zhang, Lu; Meng, Fanjun; Song, Wen; Ren, Xiaohua; Wang, Jinxin; Cai, Xiao; Li, Xuguang; Li, Yanfei; Yan, Liangguo
Abstract: To enhance the selective removal and phosphate recycle in the presence of high-strength nitrate, a novel wheat straw anion imprinted biosorbent (SAIB) was prepared by quaternization reaction and ion-imprinting technology. As the concentration of nitrate increased from 50 to 150 mg/L, SAIB exhibited the raising removal efficiencies of 106–112 % for the phosphate and the increasing selectivity coefficients of 1.57–3.93. In contrast, only 2.96–9.17 mg/g of nitrate was removed by SAIB in the binary solvent system, while that of 42.92–75.76 mg/g in the unitary solvent system. Through the analysis of functional groups, variations of solution pH and zeta potential, and theoretical calculation of density functional theory, the adsorption mechanisms of SAIB were coordinated with the electrostatic attraction and anion exchange of the imprinted cavity. The maximum adsorption capacity of SAIB for phosphate calculated from the Langmuir model was 23.86 mg/g at 45 °C and pH = 5. Additionally, the phosphate adsorption efficiency can maintain above 80 % after 4 cycles of regeneration, indicating this biosorbent has good reusability and potentials for soil fertility restoration by properly returning to the field. Overall, this biosorbent of SAIB has a wide range of application prospects in water treatment, such as eutrophication of water bodies, agricultural wastewater, and domestic sewage. Graphical Abstract: ga1 Highlights: Facile integration of quaternization and ion-imprinting for adsorbent synthesis. Excellent selectivity to phosphate in the presence of high-strength nitrate. The stability and selective adsorption mechanisms of SAIB were explored. High-value utilization of agricultural by-products.